Liver transplantation for hepatocellular carcinoma in a patient with hereditary hemorrhagic telangiectasia: a case report - Xu, Jiawei; Yu, Decai (Frontiers in Surgery, 2026)
BackgroundHereditary Hemorrhagic Telangiectasia (HHT) is a rare autosomal dominant vascular disorder causing systemic arteriovenous malformations (AVMs). Hepatocellular carcinoma (HCC) is a common malignancy, and liver transplantation (LT) serves as a curative option for advanced HCC meeting specific criteria. However, the coexistence of HHT and HCC is extremely rare, and HHT-related hepatic vascular abnormalities combined with the risk of AVM recurrence after LT pose unique management challenges. Few cases of LT for HHT-associated HCC have been reported worldwide; herein, we present one successful case.Case descriptionA 62-year-old Chinese man was diagnosed with HHT type 2 (harboring an ACVRL1 gene mutation) and Barcelona Clinic Liver Cancer (BCLC) stage B HCC. Preoperative imaging revealed a 55 mm × 32 mm HCC lesion in the right hepatic lobe, along with HHT-related intrahepatic vascular anomalies. He underwent orthotopic LT using a deceased donor liver. Intraoperatively, a “tension-free end-to-end anastomosis” technique was applied to address anomalous hepatic arteries, with real-time Doppler ultrasound monitoring to ensure vascular patency. Postoperatively, an immunosuppressive regimen based on mammalian target of rapamycin (mTOR) inhibitor was administered. The patient recovered uneventfully, with normalized liver function indicators and no evidence of HCC recurrence or HHT-related complications at the 6-month follow-up.ConclusionsLiver transplantation is safe and effective for HCC complicated by HHT. Successful management relies on comprehensive preoperative evaluation of vascular anomalies and AVMs, intraoperative individualized vascular management, and postoperative immunosuppression combined with close monitoring. Favorable short-term outcomes can be achieved with this strategy.